Peer-led group tele-supervision of clinical psychologists: optimization of resources; a Malaysian case study - Umi Izzatti Saedon; Pang, Nicholas Tze Ping; Loo, Jiann Lin (Universiti Malaysia Sabah, 2020)
Inaccessibility to clinical supervision is an issue faced by solo clinical psychologist practitioners. Combination use of web-based instant messaging and video call application were tried by 28 clinical psychologists in conducting a peer-led group tele-supervision to address ethical dilemmas, discuss case management, provide technical instruction, explore resistance and analyse countertransference, provide emotional support, and share knowledge and updated guidelines. Despite facing challenges including difficulty in face-to-face session scheduling, limited time for in-depth discussion, internet connection issues, and documentation dilemma, we believe it has potential to influence supervision practice for clinicians working in isolation in rural or remote locations.